Accessing N‐Stereogenicity through a Double Aza‐Michael Reaction: Mechanistic Insights. Issue 1 (24th November 2015) - Kohrt, Sonja; Santschi, Nico; Cvengroš, Ján
Abstract: Further development of the chemistry and applications of chiral compounds that possess configurationally stable stereogenic nitrogen atoms is hampered by the lack of efficient strategies to access such compounds in an enantiomerically pure form. Esters of propiolic acid and chiral alcohols were evaluated as cheap and readily available Michael acceptors in a diastereoselective synthesis of N‐stereogenic compounds by means of a double aza‐Michael conjugate addition. Diastereomeric ratios of up to 74:26 and high yields were achieved with (−)‐menthyl propiolate as a substrate. Furthermore, a detailed mechanistic investigation was undertaken to shed some light on the course of this domino transformation. Kinetic studies revealed that the protic‐solvent additive acts as a Brønsted acid and activates the ester toward the initial attack of the tetrahydrodiazocine partner. Conversely, acidic conditions proved unfavorable during the final cyclization step that provides the product. Abstract : TB or not TB : Cheap chiral esters of propiolic acid afford Tröger base (TB) analogues with a modified bridge in high yields and diastereomeric ratios of up to 74:26 in a diastereoselective double aza‐Michael addition (DAMA) reaction to tetrahydrodiazocines. Mechanistic studies disclosed that a protic solvent as an additive facilitates the first intermolecular step, but acidic conditions proved unfavorable during the second intramolecular conjugate addition.